Internet Analysis of Figurative Language in Automotive Advertisement Slogans - Atmaja, Karta (State institute of islamic studies salatiga, 2022)
This study aims to figure out what figurative language was utilized in the slogan and assess what that figurative language means in context. The data for this study came from advertising on the internet. The data were analyzed using descriptive qualitative research methods. Qualitative research methods focus on features of a problem's in-depth understanding. This study collects, analyzes, and interprets data through data gathering techniques such as observation and document analysis. In this study, the researcher analyzed twenty-two automotive brand slogans. It showed that there were three slogans using Personification, two slogans using Metaphor, seven slogans using Hyperbole, three slogans using Metonymy, one slogan using Simile, one slogan using Litotes, one slogan using Paradox, one slogan using Synecdoche, and one slogan using Symbols. From these results, it can be concluded that the most widely used figurative languages in the automotive advertising slogans studied are Hyperbole, Personification, and Metonymy. Keywords: Figurative Language, Analyzes, Automotive, Slogan